College Student Perception towards Sustainable Environment: Learning Opportunities after Covid-19 - Gunansyah, Ganes; Ariadi, Septi; Budirahayu, Tuti (FKIP Universitas Lampung, 2022)
Student Perception of the Sustainable Environment: Learning Opportunities After Covid-19. Objective: This study aims to determine students' perception as prospective educators at the basic education level on environmental issues and the orientation of sustainable environmental education in universities after the Covid-19 pandemic. Methods: This study uses a quantitative analysis approach with a survey method. The population in this study were students of the Department of Elementary School Teacher Education, amounting to 880 people. The number of samples taken was 249 from four generations spread from 2020, 2019, 2018, and 2017—data collection using a questionnaire with an electronic google form format. The data analysis technique used descriptive statistics. Finding: The results showed the diversity of students' perceptions of environmental problems and the need for sustainable environmental learning practices. Conclusion: In conclusion, although it is still limited, students can already see the relationship between environmental issues with economic, social, and political dimensions. Critical environmental learning is needed to improve the quality of sustainable environmental education. Keywords: Environmental Literacy, sustainable environment, student perception.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202235